The Effect of Surfactants on Separation of Light Rare Earth Metals using Emulsion Liquid Membrane Method: Review - Dwi Ratna Setiani; Afifah R. Widianti; Fauzia Salsabila; Anni Anggraeni; Husein H. Bahti; Uji Pratomo (Jurnal Akademika Kimia, 2022)
Rare earth metals (REM) are scarce elements and are only found in the form of complex compounds of phosphate and carbonate. REM consists of 17 elements classified into light REM, medium REM, and heavy REM. This article is focused on lightweight REM, which is widely applied in various industrial fields. Many REM applications are increasing the demand for high-purity and bulk REMs. However, REM has almost the same physical and chemical properties, making it difficult to separate. Therefore, the separation of REM is interesting to study with various methods, one of which is Emulsion Liquid Membrane (ELM). ELM is developing a solvent extraction method involving three phases: the external phase, the internal phase, and the membrane phase. The key to the success of ELM lies in the stability of the emulsion, which is very dependent on the type and concentration of surfactants, so in the ELM process, it is necessary to choose the right concentration and type of surfactant. Therefore, this article was made to know the effect of surfactants such as span-80, span-85, and T154 in separating light REM using the ELM method.